World Society of Emergency Surgery-American Association for the Surgery of Trauma Guidelines for management of Clostridioides (Clostridium) difficile infection in surgical patients: An executive summary. Issue 2 (11th August 2021) - Sartelli, Massimo; Ansaloni, Luca; Biffl, Walter A.; Coccolini, Federico; De Simone, Belinda; Leppaniemi, Ari; Kluger, Yoram; Tolonen, Matti; Moore, Ernest E.; Catena, Fausto
ABSTRACT: In the last three decades, the dramatic worldwide increase in incidence and severity of Clostridioides difficile infection (CDI) (formerly Clostridium difficile infection) has made CDI a global public health challenge. Surgery is a known risk factor for development of CDI yet surgery is also a treatment option in severe cases of CDI. The World Society of Emergency Surgery guidelines for management of CDI in surgical patients were published in 2015. In 2019, the guidelines were revised and updated according to the grading of recommendations assessment, development and evaluation methodology. This executive summary is intended to consolidate knowledge on the management of CDI focusing on aspects that a general and emergency surgeon should know about the prevention and the management of CDI, by providing a practical and concise version of the original guidelines.